Sustainability analysis of irrigation water management in Punjab, Pakistan - Abid, M.; Hafeez, Mohsin; Watto, M. A. (Springer, 2021)
Water management in the irrigation-dominated Indus Basin of Pakistan is under pressure to ensure equitable, long-term, stable and flexible water supplies for meeting crop water demands, growing non-agricultural water demands (domestic and industrial supplies), and minimising adverse environmental impacts of one of the largest irrigation systems in the world. In this chapter, we focus on the irrigation system in Punjab by carrying out a sustainability analysis of its current irrigation water application methods. Cai et al.’s (Sustainability analysis for irrigation water management: concepts, methodology, and application to the Aral Sea region. Environment and production technology division, discussion paper no. 86, International Food Policy Research Institute, Washington, DC, 2001) analytical framework is used, which comprises indicators of risk and vulnerability, environmental system integrity, and economic acceptability and equity. The analysis suggests that irrigation water management in Punjab is currently unsustainable due to declining surface water supplies and excessive pressure on groundwater to support intensive agriculture and increasing demand from non-agricultural uses. Furthermore, climate change projections suggest reduced overall water availability leading to reduced crop productivity. Groundwater exploitation, unsustainable irrigation and agricultural practices, and industrial effluents are affecting water quality and worsening the overall health of the Indus Basin and its ecosystem. The cost of irrigation water management is economically not viable due to the high level of subsidies for technological interventions at the farm level and minimal water charges. The gap between collected water charges and overall operation and maintenance costs has reached USD 76 million. Water productivity in the Punjab is one of the lowest in the South Asia region due to use of traditional irrigation practices with low irrigation and application efficiency. Equitable distribution of water in the province has become a big challenge for water managers given increasing water allocation conflicts, especially between upstream and downstream water users. We thus suggest adopting an approach that is more inclusive of all major stakeholder interests keeping in view the competing inter-sectoral water demands in future and the ongoing challenges of climate change, urbanisation and economic growth. Such efforts are required to improve water use efficiency as well as equity in the distribution of water among users.